A histopathological analysis of prevalence of various heart diseases: an autopsy study - Garg, Shilpa; Hasija, Sonia; Sharma, Puja; Kalhan, Shivani; Saini, Neerav; Khan, Anam (International Journal of Research in Medical Sciences, 2018)
Background: Objective was to study the histopathological spectrum of heart diseases in autopsy specimens, that play a major role as cause of death. Methods: During the period from October 2015 to October 2017. Total 170 medicolegal autopsies were received during this period. Out of 170, specimens of heart were 150. Nine specimens were autolyzed. So, 141 specimen of heart were included in the study. Gross and microscopic findings on H and E stained sections were studied. Results: out of 141 cases, 78 cases showed atherosclerosis, 20 cases showed features of myocardial infarction, myocardial hypertrophy was found in 10 cases, 5 cases revealed myocarditis, pericarditis in 4 cases and one case each of infective endocarditis and aortic stenosis. In 22 cases, there was no identifiable cause of death even after complete gross and microscopic autopsy was performed. Conclusions: Myocardial infarction due to atherosclerosis is probably the commonest finding in death cases subjected to medicolegal autopsies.